2011
DOI: 10.3852/10-266
|View full text |Cite
|
Sign up to set email alerts
|

Tulostoma domingueziae sp. nov. from Polylepis australis woodlands in Córdoba Mountains, central Argentina

Abstract: The new species, Tulostoma domingueziae, is described and illustrated. It was found in Polylepis australis woodlands in central Argentinean highlands. Tulostoma domingueziae is characterized by the combination of a warty exoperidium, contorted stipe covered by thin scales that break off, mouth slightly projected and the socket with up to six dentate hanging membranes. DNA sequence data demonstrated that T. domingueziae is distinct from Tulostoma species for which sequence data are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…But species of Tulostoma are not restricted to arid regions only. Studies in the Tropics and temperate woodlands have indicated the presence of new species, growing in shaded, humus-rich, or even humid conditions (Hernández-Caffot et al 2011). In Europe, there are also a few species that are adapted to grow in shaded and more humid conditions as T. fulvellum, T. lloydii, T. niveum, and T. squamosum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But species of Tulostoma are not restricted to arid regions only. Studies in the Tropics and temperate woodlands have indicated the presence of new species, growing in shaded, humus-rich, or even humid conditions (Hernández-Caffot et al 2011). In Europe, there are also a few species that are adapted to grow in shaded and more humid conditions as T. fulvellum, T. lloydii, T. niveum, and T. squamosum.…”
Section: Discussionmentioning
confidence: 99%
“…ITS sequence data of the type specimens of T. domingueziae (HQ667597) and T. ahmadii (KP738712) were taken from GenBank (Hernández-Caffot et al 2011, Clark et al 2016. Specimens were selected with the aim to cover all the species known to occur in Europe and from a broad geographic distribution within the area.…”
Section: Taxon Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a diverse woody mushroom genus common in deserts of the southwestern United States ( Hernandez Caffot et al 2011 ). This specimen was found growing on sandy soils on top of the plateau immediately southwest of MDRS.…”
Section: Checklistsmentioning
confidence: 99%